Reasons for choosing medical profession as the career among medical college students in Kancheepuram district - R., Ramya M.; N., Lakshmi; P., Balamurugan; Nambiar, Soumya (International Journal Of Community Medicine And Public Health, 2020)
Background: A career in medicine is one of the most respected and highly rated professions among most of the parents and students. It has been observed that many of the students choose medicine due to parental pressure and many more can’t prefer the course due to financial problems. Hence the present study was conducted to find out the reasons for choosing medical profession as career among the medical college students. Methods: A cross sectional study was conducted among 300 undergraduate medical students of Karpaga Vinayaga Institute of Medical Science and Research Centre from October to November 2019 with a pretested semi structured questionnaire. Data were entered in Microsoft Excel sheet. Analysis was carried out by using SPSS version 23. Results: The mean age of the students was 20.79±1.3 and majority of them were females (60.3%). Majority (76%) of the students chose MBBS out of self-interest. 45% of the students chose the medical profession for saving life which gives them immense happiness. 18% of the students felt regret for choosing medical profession out of which 76% had stress as the reason for regretting the medicine career. 95.7% students wanted to pursue postgraduation. Conclusions: Self-interest or a passion for the medical profession was the most common reason for choosing medicine as the career. Few students felt regret for choosing medicine as the course due to stress and lifelong reading. Special attention and counselling are needed to be given to such students and also need to encourage them to have a successful life.